Adnexal Torsion during Pregnancy Diagnosis, Treatment, and Prognosis - Rong Xu; Heng Zhang; Zhilong Yang (Clinical and Experimental Obstetrics & Gynecology)
Objective: Adnexal torsion, a rare gynecological emergency, occurs in 10–20% of adnexal cases during pregnancy, and the risk is fivefold greater for pregnant women than for their non-pregnant counterparts. Pathological variations include ovarian-tubal, solely ovarian, and solely tubal torsion. Mechanism: Ultrasound examination stands out as the accurate, safe, and readily available primary method for assessing adnexal torsion during pregnancy. Treatment approaches encompass both conservative and surgical interventions, with surgery being the mainstay for definitive diagnosis and management. The evolving trend toward minimally invasive techniques has led to elevated laparoscopic surgery being the preferred method for addressing surgical diseases during pregnancy. Findings in Brief: Laparoscopic surgery offers several advantages, such as minimal trauma, reduced bleeding, diminished postoperative pain, faster recovery, lower thromboembolic event incidence, and shorter hospital stays. Furthermore, laparoscopy provides superior exposure to the surgical field in pregnant women, minimizing uterine disturbance and subsequently lowering the risks of miscarriage, preterm labor, and premature rupture of membranes. Conclusions: A nuanced approach is needed for patients with adnexal torsion during pregnancy, where ultrasound serves as a crucial diagnostic tool and surgical intervention, especially through laparoscopy, emerges as a favorable therapeutic strategy. The benefits of laparoscopic surgery extend beyond effective treatment to encompass reduced maternal risk and improved postoperative outcomes, making it a preferred option for managing adnexal torsion during pregnancy.